Revitalisasi Kewenangan Pengelolaan Pertambangan Oleh Pemerintah Daerah Dalam Mengoptimalisasi Pelaksanaan Otonomi Daerah di Bangka Belitung - Yolanda Oktavia; Nandini Putri; Ana Apriliana; Ranita Ranita (JURNAL PENELITIAN SERAMBI HUKUM, 2023)
This research uses normative, or in other terminology, juridical-normative methods. It is a method with a statutory approach to find out the norms of das sollen, and its implementation in das sein in the community. The main objective of the research is to determine the effectiveness of norm enforcement, as well as find solutions to support the reformulation of rules to be more prospective in the future. The analysis was conducted by finding the relevance of supporting data during the era of the implementation of regional autonomy in the mining sector in Bangka Belitung, identifying policy weaknesses that caused various problems, and solutive efforts made by both the central and regional governments. From this research, it is known that after the implementation of regional autonomy, the Bangka Belitung government has established a number of regulations that support the freedom of the community to mine. Although able to provide economic benefits, this has resulted in the mushrooming of illegal miners and massive natural damage. After the stipulation of Law No. 3 of 2020 concerning Mineral and Coal and Presidential Regulation No. 55 of 2022, a number of authorities were divided between the central and regional governments. By optimizing its authority, local governments can produce a good tin mining ecosystem and be oriented towards the implementation of good regional autonomy. Keywords: : authority, mining management, regional autonomy, decentralization